2015
DOI: 10.1002/anie.201502405
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Hydroaminocarbonylation of Alkenes with Amines: A Strategy to Overcome the Basicity Barrier Imparted by Aliphatic Amines

Abstract: A novel and efficient palladium-catalyzed hydroaminocarbonylation of alkenes with aminals has been developed under mild reaction conditions, and allows the synthesis of a wide range of N-alkyl linear amides in good yields with high regioselectivity. On the basis of this method, a cooperative catalytic system operating by the synergistic combination of palladium, paraformaldehyde, and acid was established for promoting the hydroaminocarbonylation of alkenes with both aromatic and aliphatic amines, which do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…Additionally, various N-alkyl linear amides 220 could be readily prepared from alkenes, aminals, and CO in the presence of a Pd catalyst under mild conditions (Scheme 63). 199 Iminium species 221 could be generated in the presence of the Pd catalyst. …”
Section: C−n Bond Cleavage Via Imine or Iminiummentioning
confidence: 99%
“…Additionally, various N-alkyl linear amides 220 could be readily prepared from alkenes, aminals, and CO in the presence of a Pd catalyst under mild conditions (Scheme 63). 199 Iminium species 221 could be generated in the presence of the Pd catalyst. …”
Section: C−n Bond Cleavage Via Imine or Iminiummentioning
confidence: 99%
“…In 2015, Huang and co‐workers investigated a novel and efficient palladium‐catalyzed strategy for the synthesis of linear amides through the aminocarbonylation of alkenes with aminals and carbon monoxide (10 atm) by using Pd(TFA) 2 as a catalyst, DPPPen as a ligand, and NH 2 CH 2 CO 2 Me⋅HCl as an additive in the presence of H 2 O in anisole at 120 °C (Scheme ) . The authors found that the reaction proceeded through cleavage of C−N bond, and the two amino groups of the aminal were efficiently incorporated into the desired amide.…”
Section: Synthesis Of Amides From Alkenesmentioning
confidence: 99%
“…pharmaceuticals,a grochemicals,p eptides,a nd polymers. [8] Indeed, ac lose look into the literature data indicates that there is ap aucity of highly chemoselective catalytic CÀC bond-forming processes [9] with improved flexibility,practicality,a nd generality that would give access to primary, secondary,oreven tertiary amides at will, including hindered substrate combinations,while avoiding the handling of carbon monoxide (CO) at high pressures [10] or well-defined and stoichiometric organometallic species, [11] among others (Scheme 1, path b). [12] As part of our interest in reductive coupling reactions, [13] we questioned whether aunified catalytic umpolung strategy through the in situ generation of carbogenic nucleophiles (II) from unactivated alkyl halides (I)a nd their coupling with isocyanates would constitute ageneric platform for preparing aliphatic amides (III;S cheme 1, bottom).…”
mentioning
confidence: 99%